Kesantunan Berbahasa Pada Siniar Deddy Corbuzier Bertema Covid 19 Sebagai Rekomendasi Dalam Penyusanan RPP Dan Materi Ajar Tingkat SMA - Eka, Nur Syawal; Meliasanti, Ferina (Peneliti.net, 2024)
This study aims to be able to identify and describe the use of politeness in language, deviations from the principle of politeness in language. This study uses a qualitative approach with a descriptive method. This study uses YouTube social media as a forum for research subjects. The subjects in this study used Deddy Zorbuzier's podcast media on YouTube. Research data obtained from the results of listening and notes. The stages of research using the preparation stage, the implementation stage and the evaluation stage. Data analysis uses data collection, data reduction, data presentation, and drawing conclusions. The research results of the data were analyzed through a pragmatic study on aspects of politeness using Leech and Rahardi's theory using six aspects of politeness deviation maxims in language. The researcher found a form of polite speech which was judged by the principle of politeness, and there were several impolite words due to several causes of impoliteness and violating the principles of politeness. Suggestions, researchers should not only use dialogue in podcasts but data from anywhere.